Pemanfaatan Limbah Padat Bungkil Kelapa Sawit sebagai Alternatif Pakan Ikan Nila (Oreochromis niloticus sp.) - Yuliyanto Yuliyanto; Rufinusta Sinuraya; Dita Kusumawati (JURNAL CITRA WIDYA EDUKASI, 2021)
Oil palm meal is one of the wastes whose utilization is still very little because it has a fairly high crude fiber, so it is necessary to use fishery EM4 for crude fiber-lowering fermentation. The fermented palm oil cake can be used as raw material for tilapia fish feed combined with other organic materials. The purpose of this study was to determine the effect of oil palm meal on the weight and length of tilapia, determine the buoyancy of the feed and the proximate content of palm oil cake feed. This research was conducted from January to September 2021 in Tulang Bawang Tengah Subdistrict, Tulang Bawang Barat Regency, Lampung and the proximate test was conducted at the Center for Quality Testing and Certification of Feed, Setu Subdistrict, Bekasi Regency, West Java. The study used an experimental method with a completely randomized design (CRD), PO treatment of ordinary feed and P1 artificial feed (fermented palm oil meal + fish meal + tapioca flour + bran). The results of the study showed that artificial feed from oil palm waste had a significant effect on weight gain and length of tilapia. Fish length began to have a significant effect at week 6 MSA. Fish weight began to have a significant effect on 8 MSA. The buoyancy of palm oil cake feed has a higher buoyancy and the proximate content of artificial feed is suitable for consumption by tilapia.